Pre-intercalation δ-MnO2 Zinc-ion hybrid supercapacitor with high energy storage and Ultra-long cycle life - He, Simin; Mo, Zunli; Shuai, Chao; Liu, Wentong; Yue, Ruimei; Liu, Guigui; Pei, Hebing; Chen, Ying; Liu, Nijuan; Guo, Ruibin (Applied surface science, 2022)
[Display omitted] •The designed zinc-ion hybrid supercapacitor (ZHSC) adopts battery and capacitor type hybrid energy storage mechanism.•ZHSC has a maximum energy density of 157.2 Wh kg−1 and ultrahigh power density of 16,000 W kg−1.•The capacity retention rate of the ZHSC after 30,000 cycles at 2 A g−1 is 80.2%. As an emerging research on multivalent zinc ion hybrid supercapacitors has been made huge leap, yet low cycle stability and low energy density are always the main bottlenecks of hybrid capacitors. The layered structure material Zn-doped δ-MnO2 to promote the insertion/extraction of zinc ions is used as the cathode and activated carbon is used as the anode exploiting battery and capacitor energy storage mechanism to increase energy density without sacrificing power density. Electrochemical measurements manifested that the assembled aqueous zinc ion hybrid capacitor has a high energy density of 157.2 Wh kg−1, a power density of 16 kW kg−1 (0.2 A g−1) and good cycling stability with 80.2% capacity retention over 30,000 charge/discharge cycles. The excellent electrochemical performance of the device is attributed to the stable layered structure of pre-zincified MnO2, which makes the insertion/extraction of Zn2+ greatly reversible. This study provides a novel strategy for new generation zinc ion hybrid capacitors.